OS LUTERANOS NO BRASIL (Revista de História Regional, 2007)
There is a number of good studies about Lutheran Churches in Brazil. But there are only few studies about Lutherans. This paper tries to organize some aspects which characterize Lutherans in Brazil during the last 175 years of their presence in this country.